A Rare Occurrence of Fibrolipoma in Oral Buccal Vestibule - C Seethalakshmi; N Aravindha Babu; P Sri Neeraja (Journal of Clinical and Diagnostic Research, 2024)
A 62-year-old man reported to the Outpatient Department (OPD) with the chief complaint of a skin growth in the lower left back tooth region for the past three years. He complained that the growth was initially small and gradually increased in size. He had no history of tenderness but had discomfort on mastication. Medical history was non significant, and his dental history revealed that the patient underwent restorations in the past and had his teeth extracted. Upon clinical examination, no extraoral abnormalities were detected